2015
DOI: 10.1111/grs.12113
|View full text |Cite
|
Sign up to set email alerts
|

Response of degraded vegetation to introduction of prescribed burning or mowing management in a Mongolian steppe

Abstract: The understanding of the effectiveness of prescribed burning and mowing as restoration tools of degraded grasslands is important for dryland rangeland management. We examined the effects of spring prescribed burning or seasonal mowing treatments on the degraded vegetation dominated by an unpalatable subshrub, Artemisia adamsii, in grazed Mongolian steppe. Spring burning was conducted in 2013, and three types of mowing treatments (spring, previous summer, and previous summer and autumn) were conducted with vary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Some scholars have demonstrated that external disturbances can affect the biomass of grassland plants (Kawada et al, 2008;Koyama et al, 2016). Our results showed that MO, MG, and HG all significantly increased plant biomass in the C. meyeriana lowland meadows (although HG reduced plant biomass in 2017, probably due to the little precipitation in that year).…”
Section: Effects Of Utilization Mode On Grassland Plant Communitiesmentioning
confidence: 53%
“…Some scholars have demonstrated that external disturbances can affect the biomass of grassland plants (Kawada et al, 2008;Koyama et al, 2016). Our results showed that MO, MG, and HG all significantly increased plant biomass in the C. meyeriana lowland meadows (although HG reduced plant biomass in 2017, probably due to the little precipitation in that year).…”
Section: Effects Of Utilization Mode On Grassland Plant Communitiesmentioning
confidence: 53%
“…The germination characteristics of A. adamsii shown in this study may contribute to the improvement of the attempt to control A. adamsii by prescribed burning (Yoshihara et al ., 2015; Koyama et al ., 2016). One of the concerns in prescribed burning is the increasing germination of some species by improving the light environment and breaking dormancy (Hatcher and Melander, 2003), implying that the germination of light-requiring seeds of A. adamsii would be induced by burning.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, pollen from Artemisia species is known as a cause of pollinosis in many parts of the world (D'Amato et al ., 2007; Tang et al ., 2015), and A. adamsii is also recognized as an allergen among Mongolians (Konagaya, 2013). Despite its harmfulness to livestock farming and human health, to date little effort has been made to control this species (but see Yoshihara et al ., 2015; Koyama et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Koyama et al. ) and to promote recovery of desirable species by artificial reseeding (Ronnenberg et al. ).…”
Section: Discussionmentioning
confidence: 99%